Characteristics Of Trade Secrets As Property Rights In The Indonesian Property Law System - Yusuf Ibrahim, Muhammad; Ochtorina Susanti, Dyah; Suhariningsih, Suhariningsih (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This research reports on a legal study of trade secrets which are part of the Intellectual Property Rights system. Legal protection is given to trade secrets in order for trade secret right holders to be able to create a climate that encourages creation and innovation to advance Indonesian industry in order to compete in the scope of national and international business. A trade secret is information that the law considers to be a property. The classification of information as a trade secret must have economic value, be unknown to the public and kept confidential by the owner. There is a problem, namely the character of trade secrets that cannot be included in the system of property law in Indonesia, because the characteristics of trade secrets do not fulfill the elements of property rights and there is no single norm that regulates the registration of trade secret rights as property rights. Jeremy Bentham and Thomas Hobbes Theory of Legal Protection and Theory of Ownership are chosen as the analytical knife, that a trade secret is a legal right, namely a property right over an intangible movable property that arises due to a registration. The implication of this is that the trade secret law does not provide legal protection and legal certainty for the right holder.